THE BILL OF EXCHANGE AS A MEANS OF PAYMENT AND SECURITY - Belovski, Vojo (Journal of process management and new technologies, 2016)
The bill of exchange is a kind of paper in order that its holder shall entitle the debtor named in the document to pay a certain amount of payments. The bill of exchange represents a means of payment and an instrument of providing the payment. It is an unconditional order given by the drawer to the drawee to pay a certain amount to the payee listed on the bill of exchange. The bill of exchange is generally a paper on the orders but it can be issued as value paper to a name. It is such promissory notes where the issuer becomes a clause not by order. The bill of exchange though it appears as a means of payment and an instrument for securing the payment it also appears as a means of international payment, because the bill of exchange can become a modern instrument of crediting and payment. With the development of the credit market and the bill of exchange becomes a means for the drawer and the drawee. This means that instead of the bill of exchange to be paid after the expiry of a certain deadline for submission of the bill of exchange the holder may sell or discount, or to pay before the deadline for submission. With this the bill of exchange becomes a toll for discount. Based on this we can conclude that the bill of exchange has the following roles: -bill of exchange serves as a means of credit; -bill of exchange serves as means of payment; -bill of exchange serves as a means for discount by.